Pengaruh Kompetensi Kepala Sekolah dan Sistem Informasi terhadap Efektivitas Sekolah - Novi Hana Lestari; Junjun Ade Permana; Kusnandi Kusnandi; Alan Rusyadi; Elly Resly; Lilis Kholisoh (Journal of Education and Teaching (JET), 2023)
The purpose of this study is to analyze and describe the effect of principal competence and information systems on school effectiveness. The research method used is descriptive with a quantitative approach. The population in this study were 60 teachers. Because the number of populations is known, then to determine the research sample is in accordance with the population itself. Data collection techniques were carried out through the distribution of questionnaires. Data processing utilizes the SPSS 17.0 (Statistical Product and Smart Solutions) program. The results showed that the competence of the principal and the information system had a positive effect on the effectiveness of the school, this means that the higher the competence of the principal and the higher the quality of the information system, the greater the effectiveness of the school.